2021
DOI: 10.1177/20503121211053953
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to diabetes self-care management and associated factors among people with diabetes in Gamo Gofa Zone public health hospitals

Abstract: Introduction: Adherence to diabetes self-care management is a lifestyle modification for people with diabetes which includes; medication, dietary practice and regular physical activity. The objective of this study was to assess the adherence to diabetes self-care management and associated factors among people with diabetes in Gamo Gofa Zone, Southern, Ethiopia, 2018. Methods: Institutional-based cross-sectional study design with a systematic random sampling technique was conducted. A total 635 diabetic partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Although this is counterintuitive at first glance, it might be due to the fact that patients who own a glucometer believe they can always monitor their blood sugar, but it is not always the case. These findings are different from those obtained in Brazil (Degefa et al, 2020), Nigeria (Enikuomehin et al, 2021), Ghana (Agidew et al, 2021), and Ethiopia (Kassa et al, 2021). A study by Schmitt et al (2013) reported that the lack of a personal glucometer or poor access to laboratories in health facilities can be attributed to irregular measurement of blood glucose amongst diabetics.…”
Section: Discussionmentioning
confidence: 73%
“…Although this is counterintuitive at first glance, it might be due to the fact that patients who own a glucometer believe they can always monitor their blood sugar, but it is not always the case. These findings are different from those obtained in Brazil (Degefa et al, 2020), Nigeria (Enikuomehin et al, 2021), Ghana (Agidew et al, 2021), and Ethiopia (Kassa et al, 2021). A study by Schmitt et al (2013) reported that the lack of a personal glucometer or poor access to laboratories in health facilities can be attributed to irregular measurement of blood glucose amongst diabetics.…”
Section: Discussionmentioning
confidence: 73%
“…The reasons for the exclusion of papers are noted in Figure 1. In total, 82 articles [27–108] were found to be eligible and data were then extracted (Supplementary Material 4).…”
Section: Resultsmentioning
confidence: 99%
“…The perceived severity of DM and its complications may influence whether an individual engages in self-care practices [ 39 , 64 66 ]. Previous studies have found that people who perceive their diabetes as more severe had better adherence to diabetic self-care practices [ 39 , 67 – 69 ].…”
Section: Discussionmentioning
confidence: 99%